Web semantics and ontology - Taniar, David; Rahayu, Johanna Wenny (Gale virtual reference library, 2006)
"This book provides an overview of current research and development activities in the area of web semantics and ontology, giving an in-depth description of different issues, including modeling, using ontologies in enterprise systems, querying and knowledge discovering of ontologies"--Provided by publisher.